Idiopathic scrotal calcinosis. Issue 3 (September 2015) - Hari Kumar, K.V.S.; Shijith, K.P.; Singh, Dalbara; Sood, A.K.
Abstract : Idiopathic scrotal calcinosis is a benign condition characterized by the extensive slow-growing nodules over the scrotal skin. The disease is of unclear etiology and is of importance due to the disfigurement. Management is mostly surgical, with removal of the entire nodules, and the recurrence rate is high. We recently encountered a patient with chronic pancreatitis with incidentally detected scrotal calcinosis. We report the same here, along with the possible etiological mechanisms of this uncommon condition.